Contributions of crust proteins to spore surface properties in Bacillus subtilis. Issue 3 (30th January 2019) - Shuster, Bentley; Khemmani, Mark; Abe, Kimihiro; Huang, Xiaoyu; Nakaya, Yusei; Maryn, Nina; Buttar, Sally; Gonzalez, Adriana N.; Driks, Adam; Sato, Tsutomu; Eichenberger, Patrick
Summary: Surface properties, such as adhesion and hydrophobicity, constrain dispersal of bacterial spores in the environment. In Bacillus subtilis, these properties are influenced by the outermost layer of the spore, the crust . Previous work has shown that two clusters, cotVWXYZ and cgeAB, encode the protein components of the crust. Here, we characterize the respective roles of these genes in surface properties using Bacterial Adherence to Hydrocarbons assays, negative staining of polysaccharides by India ink and Transmission Electron Microscopy. We showed that inactivation of crust genes caused increases in spore relative hydrophobicity, disrupted the spore polysaccharide layer, and impaired crust structure and attachment to the rest of the coat. We also found that cotO, previously identified for its role in outer coat formation, is necessary for proper encasement of the spore by the crust. In parallel, we conducted fluorescence microscopy experiments to determine the full network of genetic dependencies for subcellular localization of crust proteins. We determined that CotZ is required for the localization of most crust proteins, while CgeA is at the bottom of the genetic interaction hierarchy. Abstract : A group of Bacillus subtilis coat proteins, encoded by cotO, cotVW, cotXYZ and cgeAB, influence spore crust structure, relative surface hydrophobicity and anchoring of a polysaccharide layer. Crust assembly is controlled by a complex set of interactions, with CotZ acting as the principal morphogenetic crust protein and cgeA at the bottom of the genetic hierarchy. CotO promotes encasement of the spore by the crust.